2016
DOI: 10.1371/journal.pone.0165381
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Games: Modeling Freeway Traffic with Game Theory

Abstract: We apply game theory to a vehicular traffic model to study the effect of driver strategies on traffic flow. The resulting model inherits the realistic dynamics achieved by a two-lane traffic model and aims to incorporate phenomena caused by driver-driver interactions. To achieve this goal, a game-theoretic description of driver interaction was developed. This game-theoretic formalization allows one to model different lane-changing behaviors and to keep track of mobility performance. We simulate the evolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 30 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…In recent years, computational modeling of social issues has been useful to understand the complexity of multidisciplinary problematics and have been taken force as simulations and modeling are good tools for prediction. The inclusion of agents characteristics and behaviors are helpful to improve previous models [8] and study emergence phenomena due to driving anger.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, computational modeling of social issues has been useful to understand the complexity of multidisciplinary problematics and have been taken force as simulations and modeling are good tools for prediction. The inclusion of agents characteristics and behaviors are helpful to improve previous models [8] and study emergence phenomena due to driving anger.…”
Section: Discussionmentioning
confidence: 99%
“…In the last three decades, traffic and human mobility in big cities have been topics of increasing interest for the social [1][2][3][4] and computer science [5][6][7][8]. These topics have been researched to understand the way that people move in the city through street networks [9][10][11][12] or public transportation networks [13][14][15], but also to understand people's behavior as they commute [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of our study include the modeling of lane changes [ 36 38 ], traffic intersections [ 17 ], and different driving behaviors [ 39 ]. Still, in previous work, we have considered each of these sophistications, so it would be straightforward to include them in future work and evaluate whether these features might affect the results presented in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling freeway traffic, [72] investigated the evolution of cooperative and defective behaviour in lane change situations. They showed that as the difference between the velocity of cooperators and defectors decreases, the fraction of cooperators increases, i.e.…”
Section: Infocommunications Journalmentioning
confidence: 99%